A Comparative Study of Self-Stigma of Seeking Help among Filipino College Students - Andrea Algen C. Dizon; Dasiree Nicole S. Mandap; Angela Ivonne S. David; Shunpel Francine R. Intal; Abigail Juliana A. Moran; Jerald Q. Vergara; Kimberly Ann S. Cantilero (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined gender differences in self-stigma of seeking psychological help among Filipino college students, which was defined as negative beliefs and attitudes that individuals have that are significant barriers to seeking psychological help for mental health concerns. This study employed a causal-comparative design. About 210 students were recruited, with an equal 105 males and 105 females. Utilizing the Self-Stigma of Seeking Help Scale (SSOSH) to assess students' attitudes or behaviors related to seeking psychological or academic help often reflects their fear of stigma or embarrassment. An independent samples t-test indicated that males reported significantly higher self-stigma (M = 2.79, SD = 0.67) than females (M = 2.33, SD = 0.61), t(208) = -5.24, p < .001, d = 0.72 (large effect). Findings suggest the need for gender-sensitive interventions to reduce stigma and promote help-seeking behavior among male students. The observation of higher self-stigma in males indicates the influence of gender norms surrounding the stigma in seeking mental health support. To address this, culturally informed programs and mental health education may help encourage help-seeking behavior and reduce the stigma.